Infecção natural por Leishmania infantum e Leishmania amazonensis e suas implicações para o controle da doença - Sanches, Letícia da Cruz [UNESP]; de Martini, Cleber Costa [UNESP]; Nakamura, Alex Akira [UNESP]; Santiago, Maria Emília Bodini; Dolabela De Lima, Beatriz; de Lima, Valéria Marçal Felix [UNESP] (FapUNIFESP (SciELO), 2016)
Leishmaniasis is a major public health problem worldwide. Because Leishmania can adapt to new hosts or vectors, knowledge concerning the current etiological agent in dogs is important in endemic areas. This study aimed to identify the Leishmania species detected in 103 samples of peripheral blood from dogs that were naturally infected with these protozoa. The diagnosis of leishmaniasis was determined through parasitological examination, the indirect enzyme‑linked immunosorbent assay (ELISA) and the polymerase chain reaction (PCR). The Leishmania species were identified by means of PCR-restriction fragment length polymorphism (PCR-RFLP). The samples were subjected to PCR using oligonucleotide primers that amplify the intergenic region ITS1 of the rRNA gene in order to identify the species. The amplified DNA was digested using the restriction enzyme HaeIII. A restriction profile identical to L. amazonensis was shown in 77/103 samples and the profile was similar to L. infantum in 17/103. However, a mixed profile was shown in 9/103 samples, which impeded species identification. In conclusion, the infection in these dogs was predominantly due to L. amazonensis, thus indicating that diagnosing of cases of canine leishmaniasis needs to be reexamined, since the causative agent identified is not restricted to L. infantum.
Natural canine infection by Leishmania infantum and Leishmania amazonensis and their implications for disease control
Keywords: Canine; Leishmania spp; Leishmaniasis; Zoonosis